2023
DOI: 10.1007/s11135-023-01793-7
|View full text |Cite
|
Sign up to set email alerts
|

What one is not: a new scale to measure Negative Party Identity in multiparty systems

Sabrina J Mayer,
Luana Russo

Abstract: The concept of negative partisanship has lately become a highly salient topic, yet its current measurements are far from optimal as they do not account for negative partisanship’s nature as a social identity, nor are they applicable to multiparty systems. In this paper, we validate the negative partisanship (NPS) scale. By relying on expert interviews, cognitive pre-tests and a large-N survey in two countries, Germany (N = 1,911) and Italy (N = 1,440), we provide a construct validation using a nomological netw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Thus, Huddy et al (2015) suggested a battery of items to capture positive partisan identity, and this has been adapted for multi-party systems by Bankert et al (2017) and Huddy et al (2018). An interesting addition to this research is the development of a scale for negative partisan identities (Bankert, 2021;Areal, 2022;Mayer and Russo, 2023). The concept of negative partisanship has been applied to European contexts using simpler measures in Mayer (2017) and Meléndez and Kaltwasser (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Huddy et al (2015) suggested a battery of items to capture positive partisan identity, and this has been adapted for multi-party systems by Bankert et al (2017) and Huddy et al (2018). An interesting addition to this research is the development of a scale for negative partisan identities (Bankert, 2021;Areal, 2022;Mayer and Russo, 2023). The concept of negative partisanship has been applied to European contexts using simpler measures in Mayer (2017) and Meléndez and Kaltwasser (2021).…”
Section: Introductionmentioning
confidence: 99%